Upaya Meningkatkan Hasil Belajar Siswa Kelas VII-B MTs Darul Amin Palangka Raya pada Pembelajaran Sejarah Kebudayaan Islam Melalui Metode Information Search - Sapuadi Sapuadi (Journal of Classroom Action Research, 2019)
The aim of this study to improve the learning achievement of class VIIB students of MTs Darul Amin Palangka Raya in learning the history of Islamic culture using information search method. This research was conducted by class action research method consisting of three steps, namely planning, implementation, and reflection. Research has been carried out in three cycles. The first cycle obtained the implementation of information searchl methods with not so good categories and learning completeness of 22.22%. The second cycle, the involvement of learning in a good category with learning completeness 74%. The third cycle, learning using information search method was carried out well and optimal completeness was 94%. Thus, it can be agreed that information search method has a positive impact on improving student learning outcomesKeywords: Information Search; Learning outcomes; Islamic History; Action Research; Cycle